1998
DOI: 10.1089/scd.1.1998.7.499
|View full text |Cite
|
Sign up to set email alerts
|

Minimization of CD34+ Cell Enumeration Variability Using the ProCOUNT Standardized Methodology

Abstract: The dose of cells expressing the surface antigen CD34 (CD34+) has been shown to be a reliable predictor of the time to engraftment following transplantation of PBPC to support high-dose chemotherapy. However, evaluation of rare cells is complicated by a number of factors, including the variability in operator and technical procedures. Recently, Becton Dickinson Immunocytometry Systems introduced a new CD34+ cell analysis system, the ProCOUNT cell enumeration kit, which automates the analysis of CD34+ cells and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 10 publications
2
8
0
Order By: Relevance
“…Firstly, the individual single‐platform approaches gave similar CVs, with all values being lower than the dual‐platform approach. Secondly, the data for ProCount users supports the findings of McNiece et al (1998 ), who observed minimal variation between operators at a single site and suggested that the ProCount kit may be useful for standardization between laboratories. However, it should be noted that ProCount, although producing the lowest inter‐laboratory CVs, still has software limitations with suboptimal samples that require operator intervention ( Peel et al , 1998 ).…”
Section: Discussionsupporting
confidence: 77%
“…Firstly, the individual single‐platform approaches gave similar CVs, with all values being lower than the dual‐platform approach. Secondly, the data for ProCount users supports the findings of McNiece et al (1998 ), who observed minimal variation between operators at a single site and suggested that the ProCount kit may be useful for standardization between laboratories. However, it should be noted that ProCount, although producing the lowest inter‐laboratory CVs, still has software limitations with suboptimal samples that require operator intervention ( Peel et al , 1998 ).…”
Section: Discussionsupporting
confidence: 77%
“…The use of TruCount tubes loaded with beads (BDIS) decreased both the inter-and intralaboratory variability when 60 specimens from HIV type 1-infected donors were shipped to five laboratories. The acquisition of cellular events along with TruCount beads has been demonstrated to be superior to standard methods in enumerating rare cells, as well as for CD34 + progenitor cells in cord blood [48] and in mobilized leukopheresis products [49] with less variability between data analyzed by different operators. The absolute DC numbers obtained by our lyse/no wash method appear to be in range with some other flow cytometric DC enumeration studies [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Thawing of CB units was performed by Rubinstein et al's method, 21 with minor modifications as described elsewhere. 9 Samples for cell counts, quantitation of CD34 ϩ cells, 22 cell viability, clonogenic assays, 23 and microbiology were drawn directly from the bag before infusion.…”
Section: Transplantation Proceduresmentioning
confidence: 99%